THE DIVIDE BETWEEN IDEALISM AND PRACTICALITY IN ANIMALS’ FUNDAMENTAL RIGHTS RECOGNITION - Susi, Mari-Ann (Pravni zapisi, 2022)
Contemporary theoretical discourse views animals as a vulnerable group, and also recognizes their capability of mental suffering. The question why this recognition has not been translated into a global and universally accepted accordance of fundamental rights to certain groups of animals is relevant for animal rights protection, while at the same time it illustrates the divide between the idealistic and normative dimensions of law. It appears that humans have known for thousands of years that at least some animals are capable of mental suffering and constitute a vulnerable group. Changes in animal rights protection have led to some changes in legislation, but these are not fundamental and do not concern the strive toward universal recognition that animals have fundamental rights. This means that there must be some other, decisive factors that are needed to move forward from the stage of vulnerability recognition to the normative development stage.